COMPARISON OF MEAN POSTOPERATIVE PAIN BETWEEN TOPICAL ANESTHESIA AND RETROBULBAR ANESTHESIA IN PATIENTS WITH PHACOEMULSIFICATION PROCEDURE FOR CATARACT SURGERY - Sharif, Ahad; Awan, Ayyaz Hussain; Khan, Sufian Ali; Shah, Mutahir; Ullah, Saif; Anwar, Adila (Journal of Ayub Medical College Abbottabad, 2024)
Background: The purpose of the study was to compare the mean post-operative pain in patients undergoing phacoemulsification for cataract with topical anesthesia vs. retrobulbar anesthesia. Methods: An interventional study was carried out in a tertiary care hospital of Islamabad. The study duration was from 30th March 2021 to 29th September 2021. The adopted sampling technique was consecutive sampling. The sample size was 180 subjects divided into two groups of 90 each. Through the use of a lottery, patients were split into two groups of 90 each. Patients in group A received topical anesthesia, whereas individuals in group B received retrobulbar anesthesia. An Ophthalmologist performed a retrobulbar block on Group B using a 23-gauge needle and 5 mL of 2% Lidocaine. The researcher observes the patients for post-operative pain. SPSS 25 version was used for statistical analysis. Results: The research study included 180 patients in total. Participants ranged in age from 40 to 70, with a mean age of 56.26±6.31 years, and 46% male vs. 54 % females. The study found the post-operative pain at 45 minutes after topical anesthesia was 0.60±0.67 and after retrobulbar anesthesia was 1.40±0.90 in patients undergoing phacoemulsification for cataract surgery. The results showed that Group A feel less pain compare to Group B and the significance value was (p .0001). Conclusion: The study concluded that topical anesthesia usually a best alternative for retrobulbar anesthesia. The patient feel less pain with topical compared to retrobulbar anesthesia.